Optimization of Tobacco Warehouse Temperature to Reduce Defects in Hand-Rolled Kretek Cigarette Products at PT XYZ - Margaretha, Natasha; Ekawati, Yurida; Oktiarso, Teguh (Teknik Industri Universitas Ma Chung, 2024)
The quality of tobacco is a critical component in cigarette production, with moisture content standards ranging from 18% to 19% to prevent production issues caused by tobacco being too dry or too moist. At PT XYZ, a cigarette manufacturing company, storage room temperature was identified as a key factor affecting tobacco moisture content. This study aimed to determine the optimal storage room temperature to maintain tobacco quality using quality control techniques and experimental design. A correlation test revealed a very strong negative relationship (91.812%) between storage room temperature and tobacco moisture content. Using a Completely Randomized Design (CRD) and a one-way ANOVA test, the analysis showed that the storage room temperature significantly impacted moisture content. The optimal temperature for maintaining tobacco quality was found to be 21˚C. These findings underscore the importance of precise temperature control in ensuring tobacco quality, contributing to improved production processes and product consistency in the cigarette industry.